2022
DOI: 10.3390/ijms232314919
|View full text |Cite
|
Sign up to set email alerts
|

From Nucleus to Organs: Insights of Aryl Hydrocarbon Receptor Molecular Mechanisms

Abstract: The aryl hydrocarbon receptor (AHR) is a markedly established regulator of a plethora of cellular and molecular processes. Its initial role in the detoxification of xenobiotic compounds has been partially overshadowed by its involvement in homeostatic and organ physiology processes. In fact, the discovery of its ability to bind specific target regulatory sequences has allowed for the understanding of how AHR modulates such processes. Thereby, AHR presents functions in transcriptional regulation, chromatin arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 216 publications
(233 reference statements)
0
6
0
Order By: Relevance
“…It has attracted great attention since the 1970s as it acts as a chemosensory protein associated with the metabolism of various xenobiotics, the activation of which can lead to toxic outcomes [3][4][5]. However, in recent decades, significant experimental evidence has revealed that the AhR is also involved in the regulation of genes governing many pathophysiological processes, including cell growth and differentiation, cell cycle and migration, apoptosis, haematopoiesis, and carcinogenesis [6][7][8][9]. Particular attention has been paid to its key regulatory roles in the immune system [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted great attention since the 1970s as it acts as a chemosensory protein associated with the metabolism of various xenobiotics, the activation of which can lead to toxic outcomes [3][4][5]. However, in recent decades, significant experimental evidence has revealed that the AhR is also involved in the regulation of genes governing many pathophysiological processes, including cell growth and differentiation, cell cycle and migration, apoptosis, haematopoiesis, and carcinogenesis [6][7][8][9]. Particular attention has been paid to its key regulatory roles in the immune system [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we would like to point out that DIF-2 and TH-DIF-1 have the same molecular weight of 293.14 and further that TH-DIF-1, a precursor of DIF-1 in vivo, possesses DIF-2-type activity in chemotaxis modulation in Ax2 cells but never induces stalk cell differentiation in HM1030 cells. These observations suggest that DIF receptors may not have strict structural specificity for ligands, similar to the aryl hydrocarbon receptor found in mammals, which can be activated by multiple lipophilic ligands [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…AHR is a pivotal player in orchestrating epigenetic regulations impacting transcriptome alterations, chromatin architecture adjustments, and involvement in crucial signaling pathways [171]. Epigenetic mechanisms such as aberrant DNA methylation, histone modification, and microRNAs can drive changes in gene expression, potentially leading to developmental programming [172].…”
Section: Othersmentioning
confidence: 99%